2018
DOI: 10.1080/09593969.2018.1556179
|View full text |Cite
|
Sign up to set email alerts
|

Customer complaint behaviour (CCB) in the retail sector: why do customers voice their complaints on Facebook?

Abstract: With the increasing usage of platforms such as Facebook, understanding customer complaint behaviour (CCB) in the context of the social media is imperative for any businesses. Of the two billion users on Facebook, more than half of its users have shared their product-related experiences with others on the platform (Logan, 2014). This paper aims to explore CCB in the context of social media in regards to customers' unfavourable buying experiences in the retail sector. A qualitative research approach and 12 in-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
0
21
0
1
Order By: Relevance
“…Not all dissatisfied consumers complain, but customers who voice their complaints can choose many ways to share their dissatisfaction with the companies and other people. In this highly connected digital era, consumers are not only receivers but also cocreators of service, and they are active communicators who share their consumption experiences via the internet (Mei et al, 2019). Social media is an appropriate environment to understand consumers since negative opinions and feelings are easily expressed online relative to the conventional surveying method (Dickinger and Lalicic, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Not all dissatisfied consumers complain, but customers who voice their complaints can choose many ways to share their dissatisfaction with the companies and other people. In this highly connected digital era, consumers are not only receivers but also cocreators of service, and they are active communicators who share their consumption experiences via the internet (Mei et al, 2019). Social media is an appropriate environment to understand consumers since negative opinions and feelings are easily expressed online relative to the conventional surveying method (Dickinger and Lalicic, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, libraries need to devote more resources for maintaining social media profiles and use these to respond to patrons' suggestions and, especially, their complaints, given the damaging effect on corporate reputation of not responding to negative reviews (Esmark Jones et al , 2018; Mei et al , 2019). Negative reviews influence consumer behaviour more than positive ones (Craciun and Moore, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the library context, research in the business sector has aimed to understand customer complaint behaviour through social media. Mei et al (2019) identified the main causes for customer complaints expressed on Facebook and concluded that having a proper procedure for managing complaints is crucial. According to their results, it is imperative to acknowledge the complaint and respond to the customer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of social media platforms has become an opportunity for companies to capture relevant information about consumers and shopping experiences, reducing access costs. However, companies should design mechanisms to process published information that does not reflect the reality of the shopping experience, which can occur because anonymous users can post comments too (Mei, Bagaas, & Relling, 2018). Nevertheless, these platforms enable companies to segment and target their consumers in more personalized and effective ways, understand their behavior and the environment they live in, and motivate changes in marketing strategies focused on the opinions of these consumers, who sometimes reach a level of precision above expert marketing specialists (Nash, 2018).…”
Section: Theoretical Framework Social Mediamentioning
confidence: 99%